Assessing Ethiopia's surgical capacity in light of global surgery 2030 initiatives: Is there progress in the past decade? - Cherinet Osebo, PhD; Jeremy Grushka, MD; Dan Deckelbaum, MD; Tarek Razek, MD (Surgery Open Science, 2024)
Background: Surgical, anesthetic, and obstetric (SAO) care plays a crucial role in global health, recognized by the World Health Organization (WHO) and The Lancet Commission on Global Surgery (LCoGS). LCoGS outlines six indicators for integrating SAO services into a country's healthcare system through National Surgical Obstetrics and Anesthesia Plans (NSOAPs). In Ethiopia, surgical services progress lacks evaluation. This study assesses current Ethiopian surgical capacity using the LCoGS NSOAPs framework. Methods: We conducted a narrative review of published literature on critical LCoGS NSAOPs metrics to extract information on key domains; service delivery, workforce, infrastructure, finance, and information management. Results: Ethiopia's surgical services face challenges, including a low surgical volume (43) and a scarcity of specialist SOA physicians (0.5) per 100,000 population. Over half of Ethiopians reside outside the 2-hour radius of surgery-ready hospitals, and 98 % face surgery-related impoverished expenditures. Lacking the LCoGS-recommended SOA reporting systems, approximately 44 % of facilities exist for handling bellwether procedures. Despite the prevalence of essential surgeries, primary district hospitals have limited operative infrastructures, resulting in disparities in the surgical landscape. Most surgery-ready facilities are concentrated in cities, leaving Ethiopia's 80 % rural population with inadequate access to surgical care. Conclusion: Ethiopia's surgical capacity falls below LCoGS NSOAPs recommendations, with challenges in infrastructure, personnel, and data retrieval. Critical measures include scaling up access, workforce, public insurance, and information management to enhance SAO services. Ethiopia pioneered in Sub-Saharan Africa by establishing Saving Lives Through Safe Surgery (SaLTS) in response to NSOAPs, but progress lags behind LCoGS recommendations.